Identificação e controle de micro-robôs móveis - Guilherme Augusto Silva Pereira (2000)
This work proposes a position controller for nonholonomic mobile robots based on classic techniques of control. The controllers project is based on linear models, determined through stochastic methods of identication based on experimental data. Besides, these models are used as predictors for compensation of dead time and consequent improvement in the response of the system. The work still proposes, a decoupling among the robot output variables, yielding independent and monovariable controllers. The suggested methodology was validated using a platform of robots' soccer, developed by under-graduate students at UFMG. The setup is constituted basically by a computer that controls, via radio, three robots observed by a computer vision system. Experimental results showed that, in spite of the difficulties imposedby the constructive aspects of this system, the proposed control presents good results and it is an adequate alternative to the complex techniques found in the literature. The proposal was implemented considered that the system will be used as platform of tests for real time cooperation of three agents playing robot soccer.